2017
DOI: 10.2196/games.6421
|View full text |Cite
|
Sign up to set email alerts
|

A Blended Web-Based Gaming Intervention on Changes in Physical Activity for Overweight and Obese Employees: Influence and Usage in an Experimental Pilot Study

Abstract: BackgroundAddressing the obesity epidemic requires the development of effective interventions aimed at increasing physical activity (PA). eHealth interventions with the use of accelerometers and gaming elements, such as rewarding or social bonding, seem promising. These eHealth elements, blended with face-to-face contacts, have the potential to help people adopt and maintain a physically active lifestyle.ObjectiveThe aim of this study was to assess the influence and usage of a blended Web-based gaming interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
6
0
5
Order By: Relevance
“…In the 6 controlled studies, 3 (50%) [ 33 , 41 , 42 ] reported that the gamification intervention had positive effects on MVPA, whereas 3 (50%) [ 34 , 36 , 37 ] reported no significant difference between the intervention and control groups. In the 3 single-group studies, the pre–post difference between the groups for time spent in MVPA was significant in 2 (67%) studies [ 38 , 46 ] but not in the study by Wilson et al [ 71 ].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the 6 controlled studies, 3 (50%) [ 33 , 41 , 42 ] reported that the gamification intervention had positive effects on MVPA, whereas 3 (50%) [ 34 , 36 , 37 ] reported no significant difference between the intervention and control groups. In the 3 single-group studies, the pre–post difference between the groups for time spent in MVPA was significant in 2 (67%) studies [ 38 , 46 ] but not in the study by Wilson et al [ 71 ].…”
Section: Resultsmentioning
confidence: 94%
“…Of the 50 included studies, 9 (18%) studies reported the time spent in MVPA. Of these 9 studies, 6 (67%) were controlled studies [ 33 , 34 , 36 , 37 , 41 , 42 ] and 3 (33%) were single-group studies [ 38 , 46 , 71 ]; the results in both were mixed. In the 6 controlled studies, 3 (50%) [ 33 , 41 , 42 ] reported that the gamification intervention had positive effects on MVPA, whereas 3 (50%) [ 34 , 36 , 37 ] reported no significant difference between the intervention and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…The blended intervention with the aim of promoting physical activity and dietary behaviors simultaneously was included. There is no consistent definition of blended intervention, and it was applied in various formats [ 25 , 26 , 29 , 30 ]. In this study, it was defined as intervention programs that include both face-to-face sessions and elements of eHealth interventions, such as a short message service (SMS), smartphone applications (APP), email, telephone counselling, a website, and a social medium.…”
Section: Methodsmentioning
confidence: 99%
“…Etäterveydenhuoltoa koskeva tutkimus on kohdistunut pääasiassa muuhun kuin työterveyshuoltoon. Työterveyshuollon alueella on tutkittu lähinnä yksilöllisten terveyden voimavarojen vahvistamista digitaalisten välineiden avulla [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Etäterveydenhuollon käyttöönottotutkimuksessa on lisäksi painottunut lääkäreiden näkökulma, vaikka muutos kohdistuu kaikkiin terveydenhuollon ammattilaisiin [22,23].…”
Section: Johdantounclassified